Implementasi Secure Hash Algorithm-256 dan Advanced Encryption Standard Untuk Verifikasi Tanda Tangan Digital - Nadimsyah, Ahmad Zaky; Ezar Al Rivan, Muhammad (Journal of Information System Research (JOSH), 2024)
Process of traditional document approval carried out across all layers of society as part of a legal system in matters related to work or daily activities that involve legal obligations by all relevant parties is done by using handwritten signatures to bind the intentions and contents of the document with all related parties and provie legal value. With the development of internet access, traditional signatures have started to be abandoned, leading to a shift in document approval infrastructure towards a hybrid system where document signing can be done electronically. This shift has introduced the potential for electronic signature forgery, as there is no validation that can be performed on a digital image of an electronic signature.The ease of scanning someone's traditional signature can potentially be misused by unauthorized parties, so digital signatures have been developed to address this problem. Digital signatures are used to secure messages or documents from unauthorised parties, secure sensitive data, strengthen the signatories' confidence and detect attempted corruption. The solution offered in this project is the development of a software system capable of verifying the authenticity of digital documents so that the documents are not abused and can be used as appropriate using the SHA-256 Hash Function and the AES-256 Encryption Algorithm. The software produced has a satisfaction percentage of 93.71%, so it can be concluded that the applications that have been developed are running well.